This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: dx = y 6 + 1 4 f Y  X ( y  x ) = f X,Y ( x,y ) f X ( x ) = 1 6 ( x + y ) x 6 + 3 4 E [ Y  X = 3 / 2] = Z 5 4 y 1 6 ( 3 2 + y ) 3 2 6 + 3 4 dy = Z 5 4 ( y 4 + y 2 6 ) dy = 325 72 1 ISyE 2027B Probability with Applications Fall 2010 f X  Y ( x  y ) = f X,Y ( x,y ) f Y ( y ) = 1 6 ( x + y ) y 6 + 1 4 E [ X  Y = 4] = Z 2 1 x 1 6 ( x + 4) 4 6 + 1 4 dx = Z 2 1 2 11 ( x 2 + 4 x ) dx = 50 33 2...
View
Full Document
 Fall '08
 Zahrn

Click to edit the document details